RYR2 Mutations Are Associated With Benign Epilepsy of Childhood With Centrotemporal Spikes With or Without Arrhythmia - Ma, Mei-Gang; Liu, Xiao-Rong; Wu, Yuan; Wang, Jie; Li, Bing-Mei; Shi, Yi-Wu; Su, Tao; Li, Bin; Liu, De-Tian; Yi, Yong-Hong; Liao, Wei-Ping (Frontiers in Neuroscience, 2021)
RYR2 encodes ryanodine receptor 2 protein (RYR-2) that is mainly located on endoplasmic reticulum membrane and regulates intracellular calcium concentration. The RYR-2 protein is ubiquitously distributed and highly expressed in the heart and brain. Previous studies have identified the RYR2 mutations in the etiology of arrhythmogenic right ventricular dysplasia 2 and catecholaminergic polymorphic ventricular tachycardia. However, the relationship between RYR2 gene and epilepsy is not determined. In this study, we screened for novel genetic variants in a group of 292 cases (families) with benign epilepsy of childhood with centrotemporal spikes (BECTS) by trio-based whole-exome sequencing. RYR2 mutations were identified in five cases with BECTS, including one heterozygous frameshift mutation (c.14361dup/p.Arg4790Pro fs∗6), two heterozygous missense mutations (c.2353G > A/p.Asp785Asn and c.8574G > A/p.Met2858Ile), and two pairs of compound heterozygous mutations (c.4652A > G/p.Asn1551Ser and c.11693T > C/p.Ile3898Thr, c.7469T > C/p.Val2490Ala and c.12770G > A/p.Arg4257Gln, respectively). Asp785Asn was a de novo missense mutation. All the missense mutations were suggested to be damaging by at least three web-based prediction tools. These mutations do not present or at low minor allele frequency in gnomAD database and present statistically higher frequency in the cohort of BECTS than in the control populations of gnomAD. Asp785Asn, Asn1551Ser, and Ile3898Thr were predicted to affect hydrogen bonds with surrounding amino acids. Three affected individuals had arrhythmia (sinus arrhythmia and occasional atrial premature). The two probands with compound heterozygous missense mutations presented mild cardiac structural abnormalities. Strong evidence from ClinGen Clinical Validity Framework suggested an association between RYR2 variants and epilepsy. This study suggests that RYR2 gene is potentially a candidate pathogenic gene of BECTS. More attention should be paid to epilepsy patients with RYR2 mutations, which were associated with arrhythmia and sudden unexpected death in previous reports.